To solve the polynomial equation \(x^3 - 4x = 0\) by factoring, we can start by factoring out the common term.
-
The equation can be rewritten as: \[ x^3 - 4x = 0 \] Factoring out \(x\), we have: \[ x(x^2 - 4) = 0 \]
-
Next, we further factor \(x^2 - 4\) as it is a difference of squares: \[ x(x - 2)(x + 2) = 0 \]
-
Setting each factor to zero gives us the solutions:
- \(x = 0\)
- \(x - 2 = 0 \Rightarrow x = 2\)
- \(x + 2 = 0 \Rightarrow x = -2\)
Thus, the solutions to the equation \(x^3 - 4x = 0\) are: \[ x = 0, 2, -2 \]
Part 1 Answer: The solutions are \(0, 2, -2\).
Graphical Check
To check the solutions graphically, you can plot the function \(y = x^3 - 4x\) and observe where it intersects the x-axis. The intersections with the x-axis correspond to the solutions of the equation.
When plotted, the graph of the function will cross the x-axis at \(x = -2\), \(x = 0\), and \(x = 2\), confirming our solutions.